دور العرف في تدبير الأراضي والمياه ببني فقوس –أولاد جرو أنموذجا - - لوبنة, ناصر (جامعة الوادي - University of Eloued, 2022)
الواقع أن دور العرف في تدبير الأراضي والمياه، لم ينل قسطا وفيرا من الدراسات التاريخية بالمغرب، فمعظم جوانبه لا تزال غامضة مجهولة، ومرد ذلك راجع لتناوله بصفة عامة. لذا خصصنا هذه الدراسة لتسليط الضوء على دور العرف في تدبير الأراضي والمياه بأولاد جرو، وقد اعتمدنا في دراستنا على المنهج الوصفي التحليلي. من أجل معالجة النزاعات القائمة على استخدام الأراضي والمياه، اعتمدت أولاد جرو نظام العرف في عملية التوزيع والتدبير، إلا أنها عرفت تحولات عميقة ساهمت في تراجع هذا النظام فيما يتعلق بتدبير الأراضي، وذلك في إطار بحث الساكنة عن أشكال جديدة لتدبير مواردها والتكيف مع التحولات التي فرضتها الظروف الراهنة. Indeed, the role of custom in land and water management, has not received a lot of historical studies in Morocco, most of its aspects are still unknown, this is generally referred. This study highlights the role of custom in land and water management in Aouled Jrou. As we relied on our study on the descriptive analytical approach. In order to address conflicts over land and water, Aouled Jrou has adopted a custom system in the distribution and management process, but it has been experienced profound transformations which have contributed the decline of the system relating to land management, as part of the population’s search for new forms of management of its resources and adaptation areas
The role of custom in land and water management in Bni Fakous – Aouled Jrou as a model -
مقال
Keywords: عرف؛ ; تدبير؛ ; مجال؛ ; قبيلة.